2018
DOI: 10.1002/asi.24098
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between health information behavior and neural processing in african americans with prehypertension

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…Although these studies suggest that improvements in neural network task differentiation would be associated with better health behaviors, none of these studies investigated this question, so it is challenging to contextualize our findings in this literature. However, as a nascent field of research, we need additional rigorous research to best understand if and how to use neuroimaging techniques to clarify the neurocognitive basis of chronic disease self-management; some of this research is ongoing (Jones et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these studies suggest that improvements in neural network task differentiation would be associated with better health behaviors, none of these studies investigated this question, so it is challenging to contextualize our findings in this literature. However, as a nascent field of research, we need additional rigorous research to best understand if and how to use neuroimaging techniques to clarify the neurocognitive basis of chronic disease self-management; some of this research is ongoing (Jones et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the neurocognitive behavioral processes associated with changes in self-management behaviors between the intervention and control groups, we designed an fMRI task to provoke our a priori regions of interest: the analytic (TPN) and empathetic (DMN) neural activation. To test our hypothesis, we developed an fMRI task that has been described in detail elsewhere (Jones et al, 2018). In brief, we designed four 7-min and 40-s (total 30 min and 40 s) video conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants viewed 48 video clips of 23 seconds in length. Each participant was exposed to the same fixed sequence design: four runs, lasting 7 minutes 40 seconds, in the same order and temporal spacing standardized using E-Prime 2.0.10 software (Psychology Software Tools, Pittsburgh, PA; Jones et al, 2019; Moore et al, 2019). The fMRI protocol has been previously described (Jones et al, 2019; Webel et al, 2019), and brain scans were performed using a Siemens 3T Skyra scanner.…”
Section: Methodsmentioning
confidence: 99%
“…This means that responses to different types of information varies depending on individual characteristics (Singh et al, 2015). One study reported findings that socio-emotional processing was positively associated with sharing of health information with others (Jones et al, 2019). Better understanding how the brain processes different types of information will help to develop individualized, and potentially more effective self-management interventions.…”
Section: Introductionmentioning
confidence: 99%